Influence diffusion model based on affinity of dynamic social network - Yun-fang CHEN; Tao XIA; Wei ZHANG; Jin LI (Tongxin xuebao)
Recently,influence maximization model is a hot issue in the field of social network influence,while the traditional independent cascade model is generally based on static network with a fixed value of activation probability.DDIC model,which was a dynamic network influence diffusion model with attenuation factor was proposed.It calculated the activation probability between nodes via affinity propagation,and according with dynamic segmentation of social network time slice,calculation of influence on proliferation of next time slice with the current time slice of activation probability performance decay.The experimental results show that the nodes in the DDIC model have more chances to active the neighbor and the average probability of activing of the DDIC model is higher.Further experiments show that influence value via computing with affinity propagation can reflect the process of the spread model more accurately.